2013
DOI: 10.1103/physrevlett.111.028303
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Field Approach for Cross-Linked Copolymer Materials

Abstract: A generalized self-consistent field approach for polymer networks with fixed topology is developed. It is shown that the theory reproduces the localization of crosslinks which is characteristic for gels. The theory is then used to study the order-disorder transition in regular networks of endlinked diblock copolymers. Compared to diblock copolymer melts, the transition is shifted towards lower values of the incompatibility parameter χ (the Flory-Huggins parameter). Moreover, the transition becomes strongly fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 57 publications
(82 reference statements)
4
51
0
Order By: Relevance
“…Figure 3 is the phase diagram for ionizable APCNs based on end-linked ionizable amphiphilic ABA triblock copolymers in oil and water as a function of the degree of ionization of the hydrophilic units and the mol fraction of the hydrophobic units. This phase diagram is in qualitative agreement with previous works on APCNs in the melt 2528 or swollen only in water 29,30 but with important differences arising from the inclusion of oil. Four of the five structures considered in this study appeared in the present phase diagram: spheres, cylinders, lamellae, and unimers in oil.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 3 is the phase diagram for ionizable APCNs based on end-linked ionizable amphiphilic ABA triblock copolymers in oil and water as a function of the degree of ionization of the hydrophilic units and the mol fraction of the hydrophobic units. This phase diagram is in qualitative agreement with previous works on APCNs in the melt 2528 or swollen only in water 29,30 but with important differences arising from the inclusion of oil. Four of the five structures considered in this study appeared in the present phase diagram: spheres, cylinders, lamellae, and unimers in oil.…”
Section: Resultssupporting
confidence: 91%
“…The ability to predict via theory or simulations the properties of these materials may facilitate the design of new-generation APCNs with better attributes and superior performance in their applications. In a relatively recent important self-consistent field approach, Schmid 25 observed that a regular APCN based on end-linked diblock copolymers (in the melt) undergoes with temperature a discontinuous transition from the disordered state to lamellae. This is in contrast to the non-cross-linked analogue in which the transition is continuous.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a general algorithm to simulate polymer networks forming reversible supramolecular linkages (e.g. [9][10][11][12][13][14][15][16][17][18] ). These are complexes that are formed, via hydrogen bonding [19][20][21] , metal-ligand interactions 22 , hydrophobic interactions 23 , π-stacking 24 , etc 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In a more general perspective, it will be interesting to explore the usefulness of the method when applied to other relevant systems like, for instance, network forming polymers. 8,9,47,48 This will deserve future investigations. 3,5,7,10,14,15,19,23,29,31,34,35,36,39,44,48,50,51,54,55,56,57,59, 60, 61, 62} along the N seg + 1 = 65 possible positions.…”
Section: Discussionmentioning
confidence: 95%